2015
DOI: 10.20863/nsd.50644
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric Curcuminoid Polyphenolics as Antioxidant and Anticarcinogenic Agents

Abstract: In this review content, it has been described the botanical and the chemical properties of turmeric (Curcuma longa), and its curcuminoid polyphenolic structures and antioxidant and anticarcinogenic influences on various cell proliferation and apoptosis. Besides it was emphasized the innovative anticarcinogen complex as boroncurcumin, and the safety evaluation with turmeric curcumin and the dose and toxicity in consuming for animals and human.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Acute heat stress significantly increased plasma TBARS but had no significant effect on SOD and ferric/reducing antioxidant power (38). Other studies have also shown that systemic increases in oxidative stress markers are likely dependent on the type of stress (39, 40).…”
Section: Resultsmentioning
confidence: 95%
“…Acute heat stress significantly increased plasma TBARS but had no significant effect on SOD and ferric/reducing antioxidant power (38). Other studies have also shown that systemic increases in oxidative stress markers are likely dependent on the type of stress (39, 40).…”
Section: Resultsmentioning
confidence: 95%
“…The formation of these complexes could have been favoured by the acidic microenvironment present in the compartment that simulated the crop and an oxalate source that could have come from the feed (Tokusoglu et al . ). CUR forms stable complexes with almost all the metals and nonmetals.…”
Section: Discussionmentioning
confidence: 97%
“…This could indicate that there was a synergistic effect between BA and CUR due to the possible formation of rosocyanine and rubrocurcumin, which are very stable complexes (Halim et al 2012;Wanninger et al 2015). The formation of these complexes could have been favoured by the acidic microenvironment present in the compartment that simulated the crop and an oxalate source that could have come from the feed (Tokusoglu et al 2015). CUR forms stable complexes with almost all the metals and nonmetals.…”
Section: Discussionmentioning
confidence: 99%
“…CR is well known to exhibit a strong antioxidant activity, as evidenced by previous in vitro and in vivo studies [35, 8892], which correlate with its anticancer and chemo-preventive actions [93]. Thus, it is anticipated that hybridization of CR with rGO-AuNP nanocomposite will yield superior anti-oxidant potential.…”
Section: Resultsmentioning
confidence: 95%